Neighbourhood communication model for enhancing trust and promoting players’ cooperative behavior: a case of iterated n-players prisoner’s dilemma - Khaled Suwais (Automatika, 2023)
Human beings collaborate when organized in an unchanging network of social relationships and if the advantage of collaboration surpasses the entire cost of collaboration with all neighbours. Cooperation may be seen in community and natural systems when selfless action is rewarded despite the risk of exclusion. Trust between neighbours is crucial since cooperative behaviour spreads more rapidly and efficiently in environments with a high trust rating. In this paper, we introduce an alternative neighbourhood communication topology to enhance the level of trust between n prisoner’s dilemma players and promote cooperative behaviour. The proposed topology allows players to communicate with their local neighbours and share their experiences within the universe of other players that are not locally connected. To understand the overall players’ behaviour locally and globally, the topology is supported by a knowledge base accessible by all players. Our topology was tested against five other communication topologies over four 1000-game tournaments. The results show that our model outperforms other strategies in promoting cooperative behaviour among participating players in small and large populations.